Growth and instability in agricultural productivity in Odisha - Asis Kumar Senapati; Phanindra Goyari (Agricultural Economics Research Review, 2023)
This paper analyses growth and instability in the productivity of major crops grown across the districts of Odisha, and examines its sensitivity to weather conditions during different phases of technological change. We find that except gram, the rate of growth in yield of other crops in the state is dismal. Productivity of rice, potato, maize, groundnut, and sugarcane has not only experienced deceleration but also witnessed instability over time. In Odisha, agriculture is largely rain-dependent and yield of crops is very sensitive to variations in rainfall. However, on adjusting for such variations, yield of most crops has shown an improvement. The analysis further suggests the role of irrigation and fertilizer in boosting agricultural growth and productivity and reducing variability. The composite index of agricultural development shows large inter-district variations. The districts have performed better during the sixties upto early eighties, a period coinciding with green revolution.